Peningkatan Profesionalisme Guru Matematika MtS/SMP Pesisir Selatan Melalui Pelatihan Merancang Penilaian Pada Kurikulum 2013 - Nasir, Wan; Utami, Nita Putri (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Situation analysis in the field illustrates that the assessment used by MTS / SMP Mathematics teachers in the 2013 curriculum has not been implemented optimally. One of the causes is the lack of understanding of MTS / SMP Mathematics teachers about the assessment in the 2013 curriculum. In addition, because there are too many SMP teachers in the South Coast, so not all teachers have received training. In other words, the prevalence of assessment training in the 2013 Curriculum. Therefore, the importance of conducting assessment design training in the 2013 Curriculum. This activity was carried out in three stages, namely preparation, implementation, and completion. The preparatory phase is carried out by coordinating with the State Junior High School in the South Coast, surveying the location of service delivery, determining the location of service, and technical preparation of training and instruments. The implementation phase is carried out with three methods, namely lecture and training, and exercises to design the assessment in the 2013 Curriculum, the last stage is analyzing the questionnaire and the work of the teacher to make a report. The results of the training activities showed that after conducting the training it was produced that 84% of teachers understood the design of the assessment in the 2013 Curriculum was obtained through questionnaires given to participants. Teachers have been able to design the 2013 curriculum assessment correctly.